COMMUNITY-BASED IRRIGATION BENEFITS DISTRIBUTION IN BANDUNG REGENCY - Putri Abdi, Azizah
The high demand for water resources is a challenge to supporting agricultural production. In this case, irrigation plays a vital role in food security. In general, the distribution of benefits from irrigation can increase agricultural productivity. However, there are issues with irrigation, such as differences in benefits received between Water User Farmers Associations (P3A) in production output and the water sources that cannot supply the water demands of agricultural land. Irrigation must benefit all, especially farmers. Therefore, this study aims to explore the distribution of economic and social development benefits and community-based management of irrigation. The case studies in this study were in the Cukang Monteng Irrigation Area, the Rawa Badak Irrigation Area, the Kiaraeunyeuh Irrigation Area, and the Juntihilir Irrigation Area in Bandung Regency, West Java, Indonesia. This research is a mixed method research with an experimental design, using primary and secondary data. This research's analytical methods are descriptive, multiple linear regression, and content analysis. The results of this study indicate that irrigation provides benefits in the form of increased production that is evenly distributed in the case study. However, water distribution has yet to be distributed relatively because of the shifting technique from upstream to downstream, so agricultural land far from water sources sometimes gets water shortages during the dry season. In terms of community participation in the four study areas, it was found that the community contributed to planning, development, management, and maintenance. However, there is no additional knowledge from farmers. Based on the regression analysis results, the variables that influence the distribution of irrigation benefits are land area, distance to water sources, and type of irrigation.